Design and optimization of an air-sparged TiO2-immobilized tubular photocatalytic reactor for the degradation of methylene blue - Ramoso, Patrick D. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
An alternative process for the removal of organic pollution in aqueous systems is photocatalysis: the challenges hindering its industrial implementation for wastewater treatment are electron-hole recombination and mass-transfer limitations. In order to address these problems, the objective of the present study is to design and optimize the performance of an air-sparged photocatalysis reactor using titanium dioxide immobilized on borosilicate glass. The performance of the reactor in the removal of the model pollutant, methylene blue (MB), was evaluated and compared against the reactor operated without sparging. The effect of mass-transfer limitations on photocatalytic activity was also modeled. Finally, optimization using Response Surface Methodology was carried out to determine the set of process parameters: initial MB concentration, treatment time, pH and sparging rate, which results to the maximum removal of methylene blue. The performance of the designed photocatlytic reactor was improved by air saprging by 40% and comparable to similar reactors in literature, but with the advantage of using a simpler immobilization technique and less expensive materials of construction. Reactor operation was found to be near the reaction-limited regime at a water flowrate of 2.8 L/min, with mass-transfer limitations minimized at the said flowrate. The set of parameters leading to the maximum methylene blue removal are 2 ppm MB, 120 minutes treatment time, pH 9.95 and 2.0 L/min sparging rate with a predicted removal of 55.5%. Validation experiments resulted to a methylene blue removal of 57.2%.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Water -- Purification -- Photocatalysis; Titanium dioxide -- Absorption and adsorption; Photocatalysis